Graduate monitoring systems in Higher Education Institutions: an integrative review (Research, Society and Development, 2022)
Higher Education Institutions (HEI) have as one of their functions to train professionals who are ready to work, and as a result, understood as the graduated student, we have the egress. The egresses are extremely important for the HEI, for they can provide valuable contributions, both as to the quality of the courses and to the formation of the current students. One alternative for the relationship between HEI and their graduates is the development and implementation of information systems and virtual portals. The objective of this article was to identify in the literature the use of information systems in the Follow-up of Graduates in HEIs, based on an integrative review. To this end, the studies were systematized in order to identify the research objectives, the theoretical approaches, the research objects, the location and the research results. The results point to the importance of information systems in the follow-up of egresses, the perceived challenges, the strategies that HEI have in the follow-up of egresses and the importance of feedback from egresses about the training received. Finally, the results demonstrate that the implementation/maintenance of an information system/portal is fundamental to follow the relationship with its egresses.